Rama Vitale, C. (2019). La virtualización de la universidad en América Latina - Vega Orrego, Daysi (REVISTA PARAGUAYA DE EDUCACIÓN A DISTANCIA (REPED), 2023)
Rama Vitale, C. (2019). La virtualización de la universidad en América Latina